Integrasi Nilai Multikultural dalam Pembelajaran Akidah Akhlak untuk Menumbuhkan Sikap Toleransi Siswa di Madrasah Aliyah Nurut Tauhid Lumajang - Sholihah, Indah Mai'syatis; Saihan, Saihan; Muhith, Abd. (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the integration of multicultural values in Akidah Akhlak learning and examine the process of fostering students’ tolerance at Madrasah Aliyah Nurut Tauhid Lumajang. A qualitative case study approach was employed. Data were collected through observations, interviews, and documentation involving the principal, an Akidah Akhlak teacher, and Grade X and XI students. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that multicultural values were integrated through three dimensions: learning content, learning methods, and the school environment. Teachers connected the topic of Asmaul Husna, particularly the attributes Ar-Rahman and Ar-Rahim, with compassion, respect, and appreciation for diversity. Collaborative discussions and question-and-answer activities encouraged interaction among students from different ethnic and regional backgrounds. In addition, the school’s policy of using Indonesian as the common language promoted inclusive communication. Tolerance was cultivated through classroom instruction, teacher role modeling, and participatory learning, reflecting Thomas Lickona’s framework of moral knowing, moral feeling, and moral action. The study concludes that Akidah Akhlak learning effectively promotes tolerance, inclusiveness, and social awareness, contributing to character development and harmonious coexistence within Indonesia’s multicultural society.